Global Climate Change and Its Impacts on Afghanistan's Climate - Haqmal, Mohammad Rozie (Journal of Natural Sciences – Kabul University)
This article examines the impacts of climate change on Afghanistan, the causes of these changes, and their potential consequences. Due to its geographical location and economic limitations, Afghanistan is considered one of the most vulnerable countries to climate change. Rising temperatures, decreased precipitation, glacier melting, and prolonged droughts have significantly affected agriculture, water resources, food security, and ecosystem stability. Predictions indicate that if greenhouse gas emissions continue, Afghanistan's annual temperature could rise by approximately 6.4°C by 2100, leading to severe environmental and economic crises. These changes will result in reduced agricultural production, declining water resources, increased internal climate migration, and worsening food security. The article emphasizes the need for adaptation, effective resource management, and international cooperation to mitigate these challenges while proposing actionable solutions. Keywords: Climate change, Afghanistan, water resources, agriculture, global warming, food security, glaciers, biodiversity, drought.